Stock Market Reactions on Returns and Trading Volume: The Impact of the Global Financial Crisis - Sohail, Asiya (2016)
Objective: This study empirically examines the short term under- and overreaction effect in the Karachi Stock Exchange, Pakistan, in the context of the 2008 Global Financial Crisis considering the period from September 2007 to 2009.Background: Investors’ probable reaction to an anticipated or unforeseen event is gaining immense importance in order to understand the complex market behavior. The arrival of good or bad news can tend to bring about a rise or decline in the stock price even if the news does not directly impact company’s performance.Method: The sample data for the stock price, trading volume and KSE 100 index are obtained from the Karachi Stock Exchange (KSE) and Securities and Exchange Commission of Pakistan (SECP) websites for the period September 2007 to 2009. To reach our objective, we used event studies.Results: There is evidence of significant overreaction in the first two weeks and significant under- reaction in the 12th and 24th week following specifically in the financial sector. For the non-financial sector, the returns stay positive and insignificant for both the winner and loser portfolios thereby negating any evidence of significant overreaction.Contributions: We wants to contribute to the existing literature, testing the under- and overreaction hypothesis in an emerging market. Our study also attempts to draw attention to any evidence of returns reversal in the loser and winner portfolios based on the trading volume. Investors may capitalize on the trading volume information to earn contrarian profits.